Embryonic olfactory learning in larvae of Smilisca phaeota (Cope, 1862) (Anura: Hylidae) (2006)
ABSTRACT: The first demonstration of embryonic olfactory learning in a tropical anuran was documented in the Colombian treefrog Smilisca phaeota. It was determined that Smilisca tadpoles learned to recognize a specific odor and preferred it over others. Embryos were exposed to the olfactory substance (orange essence) in two different ways; first, an artificial stimulation involving injection of the substance into the egg; and second, a “natural” exposure mixing the odor in the water surrounding the developing embryo. Learning capacity was evaluated in an aquarium where two olfactory stimuli were presented, the odor experienced as embryos and a novel odor. Olfactory influence prior to hatching simultaneously created in the individuals an avoidance behavior toward the novel odor. In this case, larvae associated preferably to neutral stimuli such as water. For each method, control embryos were exposed to saline solution and water.